1993
DOI: 10.1159/000310434
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Error in Computerized Pachymetry

Abstract: In a polycentric study, the influence of some of the most common variables capable of influencing the reliability of prekeratotomy pachymetry has been evaluated. The fluctuation in a sequence of measurements from the same point on the cornea with the patient in different positions (orthostatic and clinostatic), during progressive drying of the lacrimal film and before and after corneal marking have been evaluated. Three operators, working randomized, used the same computerized pachymeter (DGH1000) to make the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…21 Only a few studies have attempted to evaluate the variability of ultrasonic pachymetry: their results show a good degree of reproducibility, although most of them involved small sample sizes or were designed to compare ultrasonic pachymetry with other methods of measuring CCT. [22][23][24][25][26][27][28][29] The aim of this study is to evaluate the variability of ultrasonic pachymeter in the clinical setting and to provide a quantitative estimate of expected CCT measurements repeated by the same or different operators.…”
mentioning
confidence: 99%
“…21 Only a few studies have attempted to evaluate the variability of ultrasonic pachymetry: their results show a good degree of reproducibility, although most of them involved small sample sizes or were designed to compare ultrasonic pachymetry with other methods of measuring CCT. [22][23][24][25][26][27][28][29] The aim of this study is to evaluate the variability of ultrasonic pachymeter in the clinical setting and to provide a quantitative estimate of expected CCT measurements repeated by the same or different operators.…”
mentioning
confidence: 99%
“…All the measurements were taken late in the morning. Recently, Stucchi et al [3] have reported how the instillation of oxybuprocain 4% associated with the prone position may cause a nonnegligible alteration in the thickness of the corneal surface, but, considering that such phenomena take place, according to the same authors, this only happens at specific hours, so it cannot significantly affect our cases.…”
Section: Discussionmentioning
confidence: 76%
“…Regarding this, the literary contribution is very poor. Even if many authors have underlined the necessity of reducing corneal pain, limiting the light beam and the number of maneuvers during measurements potentially capable of altering the corneal hydration status, only a few of them have quantified the entity of that phenomenon [1,2,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for this observation lies in the fact that the left eyes had more time between instillation of anesthetic eye drops and the CCT measurement than did the right eyes, possibly leading to greater drying of the cornea on the left. Stucchi et al 29 described the role of corneal surface hydration in ultrasound pachymetry. Additionally, there might be more variability in the CCT measurement of a left eye by a right-handed examiner.…”
Section: Discussionmentioning
confidence: 99%